2007
DOI: 10.3349/ymj.2007.48.2.274
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hepatitis C virus infection on insulin resistance in chronic haemodialysis patients

Abstract: PurposeTo investigate the contribution of HCV infection to insulin resistance in chronic haemodialysis patients.Materials and MethodsThe study was performed with 55 patients who were on regular haemodialysis therapy three times per week. Of the 55 patients, 34 (20 females and 14 males with an average age of 40.9 years) were anti-HCV (+) and were defined as the HCV (+) group. The remaining 21 patients (8 females and 11 males with an average age of 50 years) were negative for HCV and other viral markers and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
4
3
0
Order By: Relevance
“…As regard age and sex distribution in our study there were no significant differences among group 1 and group 2, these results were in agreement with Tsai et al, [11] and Ozdemir et al, [12] . In comparison of clinical data of group 1 and group 2, therewere no statistical significant differences between the two groups regarding height, systolic blood pressure and diastolic blood pressure.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As regard age and sex distribution in our study there were no significant differences among group 1 and group 2, these results were in agreement with Tsai et al, [11] and Ozdemir et al, [12] . In comparison of clinical data of group 1 and group 2, therewere no statistical significant differences between the two groups regarding height, systolic blood pressure and diastolic blood pressure.…”
Section: Discussionsupporting
confidence: 83%
“…We found special laboratory tests of group 1 and group 2 showed that there were no significant differences between the two groups regarding fasting insulin, fasting C peptide, fasting glucose, HOMA-IR and insulin resistance. These results are in agreement with Tsai et al, [11] and Adam et al, [19] , and against Ozdemir et al, [12] and this can be explained by other factors played role in our study including efficacy of dialysis, relatively small number of patients and BMI was significantly higher in group 2. As regard HOMA-IR in between low URR subgroups in group 1 versus group 2 and in between high URR subgroups in group 1 versus group 2 there were no significant differences but HOMA-IR was significantly higher with low URR subgroup of group 1 versus high URR subgroup of group 1.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…HOMA-IR closely mirrors the clamp technique in the assessment of insulin sensitivity in subjects with various degrees of glucose tolerance and insulin sensitivity, also in type 2 diabetic patients treated with hypoglycemic agents [30,31]. HOMA-IR has also been applied to nondiabetic patients: with end-stage renal disease [32,33], treated with IHD [33][34][35][36][37][38][39][40][41][42] or peritoneal dialysis [42][43][44][45][46]. Shoji et al [47] demonstrated the usefulness of HOMA-IR to assess insulin resistance in renal failure patients; they also included insulin users into the study.…”
Section: Discussionmentioning
confidence: 98%
“…IR was defined as the upper quartile of HOMA-IR. Values above 2.5 were taken as abnormal and reflect insulin resistance (Ozdemir et al, 2007). Bipolar patients with diabetes (n = 21) were excluded in the HOMA-IR analysis.…”
Section: Homa-ir Determinationmentioning
confidence: 99%